Self-organised localisation in indoor environments using the ALF framework. (1st January 2013) - Eckert, Juergen; German, Reinhard; Dressler, Falko
We present and discuss the autonomous localisation framework (ALF), a self-organising indoor localisation environment. Location awareness is an important property for a growing number of applications. GPS is frequently used to provide this information in outdoor environments, but this is not applicable for indoor applications. There have been many approaches to solve the localisation problem for those GPS-denied scenarios. However, many of them are limited to certain hardware restrictions or do not provide robust self-localisation in dynamic real world application. ALF is a complete and modular framework based on minimal hardware requirements. The system is not only capable to deploying itself autonomously in unknown environments and offering position information among the participants, but it also supports accurate real-time localisation to customers. The concepts allows to remove or to add features (e.g., the heading of nodes or certain real-time capabilities) as the scenario demands or the even the used hardware changes. The awareness and handling of measurement errors, especially in non-line of sight (NLOS) cases, is an essential criterion for a real world application.